Inaugural letter for the International Journal of Financial Studies (IJFS) - Nicholas Apergis (International Journal of Financial Studies, 2013)
The honor of becoming the Editor-in-Chief of the International Journal of Financial Studies becomes immediately muted by the intensity of the task ahead. I am pleased and flattered to follow in the footsteps of previous editors and to continue to define international financial research. My ambition as well as the IJFS's ambition is the journal to become a more recognized top tier journal, acclaimed for defining new direction in financial research. Achieving this goal will require persistence of purpose, time and patience. History will judge whether within the next few years IJFS will emerge as an important financial journal publishing research, which will redirect and redefine research in financial issues.
Keywords: 330